Implementasi Konseling Berbasis Teknologi dan Pelatihan Soft Skills dalam Pengembangan Karir Anak Panti Asuhan: Studi Kasus di Panti Asuhan 'Aisyiyah Tunas Harapan: Implementation of Technology-Based Counseling and Soft Skills Training in Career Development for Orphanage Children: A Case Study at Tunas Harapan Orphanage - Imran, Yusida; Hazilina, Hazilina; Kurani, Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This community service program conducted at the Tunas Harapan Orphanage in Pontianak aims to enhance the career understanding and skills of orphanage children through career guidance and the use of appropriate technology. The program includes various training activities such as job search skills, peer counseling, and career planning. The implementation of crowdfunding websites was also introduced as part of technological innovation to support sustainable career guidance and fundraising efforts. The methodology involved socialization, skill training, psychological testing, and evaluation through assessment forms completed by participants after each training session. The evaluation results indicate significant improvements in the participants' understanding, particularly in job search skills and self-awareness, with average scores of 4.3 and 4.2 on a scale of 5. However, the evaluation also revealed that career and educational planning needs further improvement. The program successfully achieved its primary goal of career development, yet improvements in career planning are necessary to ensure the children have a clearer path for their future. Further programs focusing on deeper career planning and enhanced technological support are recommended for future community service initiatives to optimize and sustain the results achieved.